2005
DOI: 10.1177/0021886305277275
|View full text |Cite
|
Sign up to set email alerts
|

Kurt Lewin on Reeducation

Abstract: In the acknowledgements of Lewin's place as the father of action research, his work on reeducation is rarely cited. Yet it is clear that much of what he understood to be central to the complex process of reeducation is critical to the process of change and underlies the philosophical principles and practice of action research. This article presents Lewin's generally neglected paper on reeducation to enable action researchers to build on and use this important paper of Lewin's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 26 publications
0
15
0
4
Order By: Relevance
“…Unfreezing allows 'the fluidity necessary for change' (Lewin, 1943d: 47-8). Lewin also believed that the learning gained better equips people for future change (Coghlan and Jacobs, 2005;Lewin, 1946a).…”
Section: Discussion: Lewin's Three Step Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfreezing allows 'the fluidity necessary for change' (Lewin, 1943d: 47-8). Lewin also believed that the learning gained better equips people for future change (Coghlan and Jacobs, 2005;Lewin, 1946a).…”
Section: Discussion: Lewin's Three Step Modelmentioning
confidence: 99%
“…Central to Action Research is the issue of choice: the voluntary participation of all concerned on equal terms and involving democratic decision-making (Coghlan and Jacobs, 2005;Lewin, 1947c;Lewin and Grabbe, 1945;McTaggart, 1994). So influential and effective has this approach to change proved that when Oreg et al (2011) undertook a meta-analysis of 60 years of the change literature, they found that participation is one of the most effective methods for ensuring the success of change initiatives.…”
Section: Insert Figure 2c Herementioning
confidence: 99%
“…As such, "the re-education process has to fulfill a task which is essentially equivalent to a change in culture" [3] (p. 59). Culture is understood analogically, referring to shared beliefs and assumptions of a group that one cannot have alone [6]. A given culture of a group enables one to incorporate new values and perceptions into daily life [3].…”
Section: Cartography and Decalcomaniamentioning
confidence: 99%
“…The experience of inadequate stereotyping will not change one's understanding of the world [13]. Individuals engage in self-examination of their own perspectives and perceptions of the world-as well as alternative ones-in order to move away from stereotyping [3,6].…”
Section: Zeit: Where Is Attachment Research Not Yet Considered Enough?mentioning
confidence: 99%
See 1 more Smart Citation